2019
DOI: 10.3390/su11153999
|View full text |Cite
|
Sign up to set email alerts
|

Resilient Forms of Shopping Centers Amid the Rise of Online Retailing: Towards the Urban Experience

Abstract: The rapid expansion of online retailing has long raised the concern that shops and shopping centers (evolved or planned agglomerations of shops) may be abandoned and thus lead to a depletion of urbanity. Contesting this scenario, I employ the concept of 'retail resilience' to explore the ways in which different material forms of shopping may persist as online retailing proliferates. Through interviews with planning and development professionals in Edmonton (Canada), Melbourne (Australia), Portland (Oregon), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Consumption has become the social habit par excellence, and urbanity, meaning intensive random encounters between people, is at the core of a sustainable urban economy [37]. The maintenance of commercial life in the historic center of the cities and disseminated by the arteries of the new neighborhoods helps at the economic, social and environmental sustainability of the cities.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption has become the social habit par excellence, and urbanity, meaning intensive random encounters between people, is at the core of a sustainable urban economy [37]. The maintenance of commercial life in the historic center of the cities and disseminated by the arteries of the new neighborhoods helps at the economic, social and environmental sustainability of the cities.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%
“…Main trends in sustainability and retail research have been identified [69], even if sustainability has received more attention in retail management practice compared to research applications [70]. Additionally, "Retail resilience" has been analyzed as the retail response to online sales [71] and, recently, has been employed to explore the ways in which different material forms of shopping in brick-and-mortar retail spaces (main street, suburban mall, and power center or retail park) may persist as online retailing proliferates [37]. However, attention has not been paid to the prospects, in terms of threats and opportunities that small merchants perceived towards an electronic intermediary offer.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%
“…Subsequent research has revealed that the choice of shopping centers is also influenced by the image and identity being created [9], the assortment of stores and goods, emotional experience [24] and the perception of sales performance and quality [25]. According to Rao (2019) [26] a shopping center (1) operates economically and (2) influences the production of urban public life [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared to other 14 traditional markets with fewer than 150 stores, Yukgeori Market is composed of 1202 stores in the largest land area (45,433 m 2 ) among the markets in the city. Rao (2019) illustrated that different retail types in terms of the spatial structure may create synergies for vibrant urban public life or, conversely, weaken public life due to strong private control [36]. Among the traditional markets in Cheongju, retail types that accommodated many stores in a single building were investigated only in two markets; in all other markets, the facades of most shops face the open streets.…”
Section: Basic Surveymentioning
confidence: 99%